From Muslim to Christian Granada inventing a city's past in early modern Spain - Harris, A. Katie 1969- (Johns Hopkins University Press, 2007)
[This book] explores how the people of Granada created a new civic identity around these famous forgeries. Through an analysis of the sermons, ceremonies, histories, maps, and devotions that developed around the plomos, it examines the symbolic and mythological aspects of a new historical terrain upon which Granadinos located themselves and their city. Discussing the ways in which one local community's collective identity was constructed and maintained, this work complements ongoing scholarship concerning the development of communal identities in modern Europe. Through its focus on the intersections of local religion and local identity, it offers new perspectives on the impact and implementation of Counter-Reformation Catholicism.